Sergs Products Incorporated a production system study - Arellano, Angelo; Bunag, Sylvia; Rivera, Charity; Rosales, James (College of Engineering, 1994)
In order to solve the problems of inventory control as requested by management, the group focused on the purchasing and warehousing procedures of the company, Serg's Products Incorporated. First, the group recommends that the company improve their vendor relations so that their scheduling problems are eliminated. Improving vendor relations will give them better leverage in getting their deliveries on time. Once they have accomplished this, they can now find which inventory control system will best work for them. Second, the group recommends that the company follow the master production schedule that the group has prepared instead of producing at capacity. This would help alleviate their storage problems by eliminating unnecessary inventories. Lastly, the group also recommends that they systematize their raw material storage areas by itemizing supply, defining pathways inside the warehouse and providing framing for their pallets.